Segment-specific regulation of epididymal gene expression. Issue 3 (September 2016) - Sipilä, Petra; Björkgren, Ida
Abstract : The epididymis is necessary for post-testicular sperm maturation. During their epididymal transit, spermatozoa gain ability for progressive movement and fertilization. The epididymis is composed of several segments that have distinct gene expression profiles that enable the establishment of the changing luminal environment required for sperm maturation. The epididymal gene expression is regulated by endocrine, lumicrine, and paracrine factors in a segment-specific manner. Thus, in addition to its importance for male fertility, the epididymis is a valuable model tissue for studying the regulation of gene expression. This review concentrates on recent advances in understanding the androgen, small RNA, and epigenetically mediated regulation of segment-specific gene expression in the epididymis.